Development of a Project of an Improved Row Cultivator that Coordinates The Processes of Row Processing and Feeding - Nazirjonovich, Khudoyarov Anvarjon; Shohrukhbek ogli, Kholdarov Muhammadjon (American Journal of Botany and Bioengineering, 2026)
In cotton cultivation, inter-row cultivation and plant nutrition are considered essential agrotechnical measures. Separate execution of these processes leads to an increase in energy consumption, repeated movement of aggregates across the field, and soil re-compaction. In this regard, the creation of resource-saving technical means that combine the processes of inter-row cultivation and plant fertilization with mineral fertilizers is a pressing scientific and practical issue. This article is dedicated to the development of a design for an improved furrow cultivator that simultaneously performs inter-row cultivation and plant nutrition. A structural diagram of the cultivator has been developed, and the main parameters influencing the mutual arrangement of working parts and the effective execution of the technological process have been analyzed. The proposed technical solution allows for the high-quality loosening of inter-row soil, the removal of weeds, and the local application of mineral fertilizers in the layer where the root system develops. As a result, the number of trips of the unit across the field is reduced, fuel consumption is reduced, soil compaction is prevented, and the efficiency of agrotechnical measures is increased.